PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT PROPERTIES OF LEAF EXTRACTS OF CARICA PAPAYA - G, NANDINI; TS, GOPENATH; PRASAD, NAGALAMBIKA; KARTHIKEYAN, MURUGESAN; GNANASEKARAN, ASHOK; MS, RANJITH; PALANISAMY, PRADEEP; M BASALINGAPPA, KANTHESH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the present study aimed at investigating the phytochemical and antioxidant properties of Carica papaya leaf extracts. Methods: As phytochemicals are biologically active compounds and a powerful group of plant chemicals, believed to stimulate the immune system along with antioxidants, the molecules which hinder oxidation of other molecules by the process of inhibiting or by generating the oxidizing chain reactions and preventing diseases. The total phenolic content (TPC) was determined by Folin-Ciocalteu method and total flavonoid contents (TFC) were determined aluminum chloride method and antioxidant by 2,2,1-diphenyl-1-picrylhydrazyl method. Results: The results of phytochemical screening revealed the presence of bioactive compounds such as alkaloid, carbohydrates, and amino acids and TPC and TFC varied among the different solvent extracts, in which methanolic extracts showed highest amount of phytochemicals and TPC and TFC and antioxidants compared to other solvents. Conclusion: The isolation and purification of specific bioactive compound may account as natural and promising medicines in exploration of new drug.